The structural characteristics of women-endorsers in advertising messages and their influence on consumers´ responses - Shcheglov, Vitalii (2018)
Participation of women-endorsers in advertising is key element in solving some of the psychological problems of the advertising industry: to involve consumers into the message of the brand, to evoke desire to possess advertised product and to form positive attitude towards brand. Researchers claim that consumers build their attitude towards brand messages based on their first impression. Human images are the first sources which consumers pay attention to in advertising. Negative reaction to these images has strong impact on consumers’ attention towards the advertising message, their interest towards the product and brand which may lead to disregarding of advertising. Study shows that image of endorsers may influence not only on attention or interest of consumers to brand but also may form their attitude towards the product and intention to purchase (Bjerke and Polegato, 2006; Chi, Yeh, Huang, 2009; Goldsmith, Laffery and Newell, 2000; Maheswaran, Durajraj and Sternhall, 1990; Solomon and Michael, 2004). On the other hand, for the consumers, the endorsers used in adverting are the most powerful vehicles for the brands’ messages because they are capable of forming the opinion of consumers through a large number of psychological effects (Bahram and Zahra, 2010; DeBono, Kenneth, Harnish and Richard, 1988; Goldsmith, Laffery and Newell, 2000). Basic modalities represented by endorsers, such as speech, emotional expression, behavior, etc., are dependent on several external and internal factors (social, cultural, political, religious, economic, and others), and therefore, they tend to vary in space and time. This complexity makes then elusive to scientific study. The purpose of this study is to define how participants’ attitudes towards different characteristics of women-endorsers influence on their assessments of brands and their messages. How participants’ assessments of these characteristics influence on responses of participants in the form of subjective feedback (such as attention, interest, positive attitude towards advertising message, brand and intention to purchase). This study shows to what extent participants’ assessments of women-endorsers are subject to influence of brand attitude in consumers and how these assessments correlate.